Health knowledge of fourth year high school students in Nueva Vizcaya - Cacacho, Maria (Guiab) 1927- (s.n.], 1974)
To educate an individual in health is to provide him with the necessary health concepts consistent with desirable behavior that will enable him to make sound and wise decisions essential for the promotion of his well-being. The goal of health education is to help each person seek a pattern of behavior which will help them attain optimal health -- avoid diseases and accidents in life. It is the purpose of this study to appraise the health knowledge of fourth year high school students in Nueva Vizcaya.